POLITICAL IMPLICATIONS OF LITHUANIAN CONCEPTUAL ART - Rimaitė, Viktorija (Politologija, 2016)
This article aims to take a closer look at conceptual art practices as platforms for expressing political attitudes. Conceptual art practices shifted the emphasis of art-making away from static, individual objects towards the presentation of a new relationship in space, time, and context. Moreover, conceptual art represents “institutional critique” in the sense of critically reflecting the art practices within galleries, including the opposition to understanding arts as consumerism. Despite the fact that conceptual art is recognised as one of the most political branches of art, there is a strong relationship between political expressions and local context. There is a wide scientific agreement that local political, social, historical, economic, and cultural conditions are the main factors responsible for political attributes. In the empirical approach evidence of visual similarities between US, West Europe, East Europe, and Latin America, the conceptual practices are explored, but the political, ideological, and social concepts are recognised as radically different. Considering the differences of political interpretations of conceptual art that depend on a particular region and the differences between individual Eastern European countries, Lithuanian case must be analysed in its own terms. However, social and political scientists are still reluctant to show more interest in the political and social field of art practices in Lithuania. This article seeks to identify the types of political implications that are being communicated in the Lithuanian conceptual art and why artists select certain attitudes and attributes at certain times. The framing of the article is designed to emphasize and outline the local specificity and political identity of artistic works that were made in Lithuania. The analysis attempts to situate the term “conceptual art” in Lithuania. Later, it leads to the isolation of four directions of political implications in the realm of Lithuanian conceptual practices. The first direction is related to the criticism of internal politics of the art world. The second one reveals a strong relationship between conceptual art practices and current problems in the public sphere, such as ecology, human rights, and environmental protection. The third direction leads to the legitimization of conceptual practices and critiques of regime, as well as pursuing and proclaiming certain political goals on the local political, social, and cultural stage. And the last one can be defined as institutionalisation and routinisation of conceptual art in Lithuania with the elimination of internal and external elements of political critique. All in all, the aim to problematize the dynamics of political communication in Lithuanian conceptual art can be defined as the main goal of this article. It reveals that artistic practices have the potential to create the subtle expressions of political and social attitudes as well as spaces for political protest in Lithuania.